2021
DOI: 10.3390/biology10090843
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Regeneration and Rehabilitation Recovery after Stroke

Abstract: Patients that survive after a stroke event may present disabilities that can persist for a long time or permanently after it. If stroke prevention fails, the prompt and combinatorial intervention with pharmacological and rehabilitation therapy is pivotal for the optimal recovery of patients and the reduction of disabilities. In the present review, we summarize some key features of the complex events that occur in the brain during and after the stroke event, with a special focus on extracellular vesicles (EVs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…Indeed, cEVs include multiple subpopulations of EVs released by all body cells, including those released by neurons and glial cells ( 97 ). It was already demonstrated their major involvement in the reparative mechanisms occurring in the brain after a lesion ( 98 , 99 ), but the complex composition of cEVs, their heterogeneity, their nanoscale dimensions and the laborious isolation and characterization methods have currently limited their application in a clinical scenario. Nonetheless, Raman spectroscopy can represent a turning point in the use of cEVs in clinics, allowing to condense in a continuous variable, information coming from multiple molecular compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cEVs include multiple subpopulations of EVs released by all body cells, including those released by neurons and glial cells ( 97 ). It was already demonstrated their major involvement in the reparative mechanisms occurring in the brain after a lesion ( 98 , 99 ), but the complex composition of cEVs, their heterogeneity, their nanoscale dimensions and the laborious isolation and characterization methods have currently limited their application in a clinical scenario. Nonetheless, Raman spectroscopy can represent a turning point in the use of cEVs in clinics, allowing to condense in a continuous variable, information coming from multiple molecular compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that EVs play an important role in the pathophysiological process of IS [ 87 , 88 ]. Researchers have found that many different cell-derived EVs have neuroprotective and nerve repair functions.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Altering inflammatory responses ( Grieco et al, 2021 ), tissue/wound healing ( Bray et al, 2021 ; Costa et al, 2022 ), and brain remodeling ( Gualerzi et al, 2021 ) are all active areas of research with EV products for both tracking and inducing regenerative processes ( Gualerzi et al, 2021 ). Inhibiting inflammation is an avid area of EV research.…”
Section: Evs As Personalized Therapiesmentioning
confidence: 99%